Visão de águia: a (trans)formação do leitor na prática de letramento ‘Pensar Alto em Grupo’ - Cichelero, Marli (2021)
This study, which is part of the Applied Linguistics area, aims to investigate the formation of the responsive reader in a continuing education course for teachers through experiences of reading the dialogical practice of Group Think-Aloud. It is a qualitative research of the interpretative stamp that brings as an assumption of auto reflection in the actions carried through by the researcher by means of the research-action. For data collection the following instruments were used: Group Think-Aloud and the use of the reflexive journal. The participants of the study were nineteen teachers of a continuing education course called “Constructing a literacy practice for the formation of readers”. Based on the epistemology of Mikhail Bakhtin’s dialogism and the studies carried out by Paulo Freire, and following questions were answered: How can the dialogic practice of Group Think-Aloud, in a continuing teacher education course, contribute to the formation of the responsive reader? How do the processes of construction of senses occur in the dialogical practice of Group Think-Aloud? How does the process of (trans)formation of the responsive reader occur? What are the practical repercussions of the Group Think-Aloud on the personal and professional lives of the teachers participating in this study? The analysis of the data set showed that Group Think-Aloud, as practice in literacy, can contribute to the (trans) formation of the reader and the traditional teaching practices of reading when the teacher uses the assumptions of Paulo Freire’s concept of dialogue and Mikhail Bakhtin’s dialogism in the process of teaching and learning reading. The freedom contained in these two concepts allows the readers and instructors a kind of awareness from the narration of their life stories and their knowledge of the world through the use of their word that also refers to other words previously said that go through a (re)meeting of their word with the other word, whether it is the reader or the author of the text. It is in this encounter that the process of construction of senses takes place. In this dialogic practice of literacy, the reading teachers walk through metonymies, dialogue with other previously constructed discourses, build a collective dialogue with the purpose of deciphering the enigmas presented in the text in the incessant search to (trans)form themselves as readers and instructors of readers. In this process of (trans)formation, some elements are necessary: time, persistence, the mobilization of knowing how to listen and the union of the participating teachers. Through oral and written reports, they reveal the repercussions of the practice of Group Think-Aloud on personal and professional life, showing that Group Think-Aloud contributes to the formation of readers with diverse ages and educational needs, and that this teaching practice can be used in diverse contexts and realities, thus providing the formation of responsive readers